2016
DOI: 10.18632/oncotarget.12025
|View full text |Cite
|
Sign up to set email alerts
|

Cyanidin-3-o-glucoside directly binds to ERα36 and inhibits EGFR-positive triple-negative breast cancer

Abstract: Anthocyanins have been shown to inhibit the growth and metastatic potential of breast cancer (BC) cells. However, the effects of individual anthocyanins on triple-negative breast cancer (TNBC) have not yet been studied. In this study, we found that cyanidin-3-o-glucoside (Cy-3-glu) preferentially promotes the apoptosis of TNBC cells, which co-express the estrogen receptor alpha 36 (ERα36) and the epidermal growth factor receptor (EGFR). We demonstrated that Cy-3-glu directly binds to the ligand-binding domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…These are compounds known to inhibit the growth and metastatic potential of breast cancer cells. Cy-3-glu directly binds to the LBD of ERα36 and inhibits EGFR/Akt signaling in TNBC cells through EGFR degradation prior to inducing apoptosis [99].…”
Section: Indirect Modulators Of Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are compounds known to inhibit the growth and metastatic potential of breast cancer cells. Cy-3-glu directly binds to the LBD of ERα36 and inhibits EGFR/Akt signaling in TNBC cells through EGFR degradation prior to inducing apoptosis [99].…”
Section: Indirect Modulators Of Expressionmentioning
confidence: 99%
“…Finally, it seems that the ERα36/EGFR/HER2 loop plays an important role in tamoxifen resistance as Yin and colleagues showed that inhibition of this loop with a dual tyrosine kinase inhibitor, lapatinib, or ERα36 downregulator Broussoflavonol B restores the sensitivity of MCF-7 cells that were resistant to tamoxifen [88,105]. Furthermore, Icaritin and Cy-3-glu are associated with EGFR-dependent signaling inhibition and apoptosis of MDA-MB-231 triple negative breast cancer cells [97,99]. Therefore, the use of these inhibitors could counteract the positive ERα36/EGFR loop in the progression of triple-negative breast tumors or the ER36/EGFR/HER2 loop in tamoxifen resistance within ERα66-positive breast tumors.…”
Section: Future Prospectsmentioning
confidence: 99%
“…The free radical-scavenging potential of anthocyanidins and its anti-inflammatory effects have been reported. Cyanidin-3- O -glucoside has been reported to display anti-tumor activity in breast cancer [ 14 ]. In addition to being rich in anthocyanidins, red lettuce is also a good source of different classes of phenolic compounds, primarily hydroxycinnamic acid, usually from caffeic acid derivatives and flavonols [ 10 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cyanidin, a compound found in fruits, is the derivative from flavonoid and flavanone (Fu, Wei, Zhou, Zhang, & Yang, ). Due to its antioxidant property, cyanidin may help prevent a variety of free oxygen radical related diseases, including cancer and cardiovascular diseases (Pantan, Tocharus, Suksamrarn, & Tocharus, ; Wang et al, ). It has been demonstrated that cyanidin‐treated preadipocytes showed abnormal morphology.…”
Section: Introductionmentioning
confidence: 99%